#TITLE_ALTERNATIVE# - OCTAVIAN PANGEMANAN (NIM 10103022) ; Pembimbing : Dr. Janny Lindiarni, RANDY
The study of inverse semigroup has begun since the 1950s, which was firstly introduced seperately by V. V. Vagner in 1952 and by G. B Preston in 1954. Later in 1973, in an important paper by H. E. Scheiblich, a construction of the free inverse semigroup that throws considerable light on their structure was given. In this thesis, the concept of free inverse semigroup construction by C. Carvalho in his disertation titled ‘Presentations of Semigroups and Inverse Semigroups’ will be discussed. The similarities between this particular construction and the construction of free group will be clear. Besides that, various algebraic structures that are related to free inverse semigroups and several examples will be studied.